Media Scrapbook Sebagai Sarana Pemahaman Materi Sumber Daya Alam di Sekolah Dasar - Muhammad Wahyu Saputra; Achmad Fathoni (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
A media scrapbook is a type of learning media in the form of a book that contains information or explanations about the material presented with pictures and decorated to attract students' attention and make it easier for students to understand the material while studying. The purpose of this study is to examine digital scrapbook learning media in Social Studies learning Natural Resources content created by SD N 1 Paulan instructors.  This is a qualitative descriptive study. The use and growth of learning media in schools as a whole was studied. Data was gathered through interviews and direct observation of the state of learning media in schools. Teachers and students were interviewed. Teachers are asked questions about the usage and development of instructional media in the social studies learning process. Furthermore, learning observations were conducted to directly determine the use of instructional media in schools; the observations also attempted to strengthen the analysis's results. Overall, this study shows that natural resource teaching materials using digital scrapbooks developed by SD N 1 Paulan teachers are considered appropriate and effective for use in the teaching and learning process. The study's implications are that (1) developed teaching materials can be used in the teaching and learning process, (2) developed teaching materials can increase teacher insight in improving quality and creating valuable learning, and (3) developed teaching materials can be used as an alternative teaching material in learning natural resource material.